2021
DOI: 10.1016/j.nmni.2021.100926
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 reinfection in patients negative for immunoglobulin G following recovery from COVID-19

Abstract: While many patients infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) eventually produce neutralising antibodies, the degree of susceptibility of previously infected individuals to reinfection by SARS-CoV-2 is currently unknown. To better understand the impact of the immunoglobulin (IgG) level on reinfection in recovered coronavirus disease 2019 (COVID-19) patients, anti-nucleocapsid IgG levels against SARS-CoV-2 were measured in 829 patients with previously confirmed infection just afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 42 publications
2
53
0
1
Order By: Relevance
“…When the two target genes (ORF1ab and E) tested positive by specific real-time RT-PCR, a cycle threshold value (Ctvalue) ≤ 36.7 was defined as a positive result and a Ctvalue of greater than 36.7 was defined as a negative result. 16,17 Ct-value is a semi-quantitative assessment that can widely show the concentration of viral genetic material in the patient samples following testing by RT-PCR. A low Ct-value indicates a high concentration of viral genetic material, which is typically associated with a high risk of severity, but a high Ct-value indicates a low concentration of viral genetic material which is typically associated with a lower risk of the disease severity.…”
Section: Reverse-transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…When the two target genes (ORF1ab and E) tested positive by specific real-time RT-PCR, a cycle threshold value (Ctvalue) ≤ 36.7 was defined as a positive result and a Ctvalue of greater than 36.7 was defined as a negative result. 16,17 Ct-value is a semi-quantitative assessment that can widely show the concentration of viral genetic material in the patient samples following testing by RT-PCR. A low Ct-value indicates a high concentration of viral genetic material, which is typically associated with a high risk of severity, but a high Ct-value indicates a low concentration of viral genetic material which is typically associated with a lower risk of the disease severity.…”
Section: Reverse-transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…A large prospective cohort study conducted in England on 25,611 individuals showed that a person with a history of previous SARS-CoV-2 infection has an 84% lower risk of reinfection during the seven months following a primary infection as compared to naïve patients [ 3 ]. In a study conducted among 829 patients recovered from COVID-19, 87 had no detectable IgG against SARS-CoV-2, of whom 25 (28.7%) were reinfected 1–3 months after their first infection, while there was just one case of reinfection 4.5 months after initial recovery among those with detectable IgG (0.1%) [ 4 ]. Recently, a meta-analysis showed that the pooled estimation of reinfection among recovered patients was 0.3%, with a high heterogeneity among studies, and it was more common among male patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Establishing reinfection prevalence is a difficult process in epidemiological studies as this requires viral sequencing from both the primary and secondary infection during large longitudinal cohorts [27], and not many studies can afford to do this on a large scale. Emerging data from a few large cohort studies [28][29][30] has shown that the prevalence of reinfection by SARS-CoV-2 lies anywhere between <1% and 5%. It is still not clear what proportion of individuals with COVID-19 get re-infected by the virus and if the protective immunity from previous infection by SARS-CoV-2 wanes over time.…”
Section: Introductionmentioning
confidence: 99%